The Effect of Digitalization and Social Media: Generation Z's Purchase Intentions for Somethinc Skincare Products in Indonesia - Lubis, Riska Azzura; Hayu, Rina Suthia (School of Business, IPB University (SB-IPB), 2025)
Background: Generation Z, as increasingly dominant consumers with unique shopping behavior characteristics, plays a vital role in the e-commerce market. Therefore, it is essential to evaluate how marketing factors such as brand image, brand credibility, brand advocacy, and electronic word of mouth (eWOM) influence their purchasing decisions, especially in skincare.Purpose: This study aims to analyze the Influence of brand image, brand credibility, brand advocacy, and electronic word of mouth (eWOM) on Generation Z's purchase intention for Somethinc skincare products in Indonesia.Design/methodology/approach: This study uses a quantitative approach and distributes questionnaires online to 260 Generation Z respondents. Samples were taken using the purposive sampling technique with a Likert Scale. Data analysis was carried out using SmartPLS.Findings/Results: The results showed that brand image and advocacy significantly influence Generation Z's intention to purchase skincare in Indonesia. In contrast, brand credibility and electronic word of mouth do not significantly positively influence Generation Z's purchase intention for skin care.Conclusion: The study's results show that digitalization and social media significantly influence company activities, especially in marketing. Referring to the research findings, companies should strengthen the brand image and advocacy through marketing campaigns highlighting the brand's unique value and encouraging customers to share positive experiences, such as loyalty programs or customer communities. On the other hand, strategies related to brand credibility and eWOM need to be re-evaluated to increase their effectiveness or shift to more impactful efforts. Thus, companies can prioritize resources on aspects that significantly drive consumer purchase intention.Originality/value (State of the art): This study's results provide insight into the effectiveness of marketing strategies in influencing Generation Z's purchasing behavior and explain the inconsistency of previous research findings. Keywords: brand image, brand credibility, brand advocacy, electronic word of mouth, purchase intention